Formation of Ferrogabbro Through Fe-Ti Oxide Accumulation Under Moderate Oxidation Conditions: Insights from the Dashanshu Intrusion in the Emeishan Large Igneous Province, SW China - Jiang, Manrong; Liu, Wenhao; Zu, Bo; Wang, Weihua (Minerals (Basel), 2024)
The mechanism of iron enrichment in ferrogabbro remains a controversial subject. This study provides valuable insights derived from the Dashanshu intrusion, located in the Emeishan Large Igneous Province in southwestern China, which features ferrogabbro with a notably high iron content (total Fe2O3 reaching up to 21.6 wt.%). The ferrogabbro samples exhibit distinctive petrographic features, including the early crystallization of plagioclase prior to pyroxenes, amphibole replacing pyroxenes, and magnetite–ilmenite intergrowth filling the interstices between plagioclase and pyroxenes. A quantitative mineral analysis based on micro-X-ray fluorescence element mapping reveals a positive correlation between Fe-Ti oxides and bulk-rock iron contents, suggesting that the formation of ferrogabbro is primarily attributed to the accumulation of Fe-Ti oxides. Petrographic characteristics combined with oxygen fugacity determinations indicate that the primitive magma had a low content of water and was moderately oxidized (ΔFMQ − 0.13 to ΔFMQ + 1.35). These conditions suppress the early crystallization of Fe-Ti oxides, thereby allowing for an enrichment of iron in the residual magma. Following the crystallization of plagioclase and pyroxenes, increased water content—evidenced by amphibole replacing pyroxenes—triggers extensive crystallization of Fe-Ti oxides. Due to their late-stage crystallization, these oxides do not settle within the magma, which possesses a high crystallinity (>50%) and consequently exhibits non-Newtonian fluid behavior. This results in the localized accumulation of Fe-Ti oxides and the formation of a ferrogabbro layer. However, the late-stage crystallization of Fe-Ti oxides also impedes the sinking and flow-sorting processes that are essential for the development of economically valuable Fe-Ti oxide layers. This may account for the lack of an economically valuable Fe-Ti oxide layer within the Dashanshu intrusion.